2018
DOI: 10.1002/rth2.12057
|View full text |Cite
|
Sign up to set email alerts
|

Factor V‐short and protein S as synergistic tissue factor pathway inhibitor (TFPIα) cofactors

Abstract: Essentials FV‐Short, a normal splice isoform of Factor V, binds tissue factor pathway inhibitor (TFPIα) with high affinity.FV‐Short functions as a synergistic TFPIα cofactor with protein S in inhibition of Factor Xa.FV‐Short is much more efficient as TFPIα cofactor than full length FV.TFPIα‐cofactor activity of FV‐Short is lost upon activation of coagulation by thrombin‐mediated cleavage. Background FV‐Short is a normal splice variant of Factor V (FV) having a short B domain, which exposes a high affinity‐bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(81 citation statements)
references
References 41 publications
3
78
0
Order By: Relevance
“…Addition of increasing concentrations of protein S gave a dose‐dependent inhibition of FXa with 50% inhibition at approximately 1.25 n m and maximal inhibition at 5 n m protein S. Similarly, the inclusion of diluted plasma in the assay instead of protein S yielded a dose‐dependent inhibition with maximum inhibition observed at 1/50 dilution and around 50% inhibition at 1/200. As we previously have reported , the TFPI α ‐cofactor effect of protein S in the assay depended on the presence of FV‐Short and in the absence of added FV‐Short, neither protein S (up to 10 n m ) (Figure S1) nor plasma (up to 1/100 dilution) yielded any stimulation of FXa inhibition.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Addition of increasing concentrations of protein S gave a dose‐dependent inhibition of FXa with 50% inhibition at approximately 1.25 n m and maximal inhibition at 5 n m protein S. Similarly, the inclusion of diluted plasma in the assay instead of protein S yielded a dose‐dependent inhibition with maximum inhibition observed at 1/50 dilution and around 50% inhibition at 1/200. As we previously have reported , the TFPI α ‐cofactor effect of protein S in the assay depended on the presence of FV‐Short and in the absence of added FV‐Short, neither protein S (up to 10 n m ) (Figure S1) nor plasma (up to 1/100 dilution) yielded any stimulation of FXa inhibition.…”
Section: Resultssupporting
confidence: 60%
“…We have recently shown that the interaction between TFPIa and FV-Short affects the function of TFPIa as inhibitor of FXa [3,26]. FV-Short in itself only weakly stimulates the activity of TFPIa but it strongly supports the TFPIa-cofactor activity of protein S. The results suggest that FV-Short and protein S act as synergistic TFPIa cofactors.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…9,74,89 Recent studies have shown that TFPIα circulates as a complex with FV and FV-short in circulation and that protein S can function as a synergistic cofactor, together with FV/FV-short, in the inhibition of FXa. 69,86,88 We have shown that protein S alone as well as protein S in complex with FV does this by enhancing the initial encounter complex binding between TFPIα and FXa. 69 It is therefore likely that a similar mechanism is involved in the enhancement by protein S and FV/FV-short.…”
Section: Tfpi Cofac Tor Fun C Ti On and F Vmentioning
confidence: 98%